Timber Engineering - Principles for Design - Blaß, Hans JoachimSandhaas, Carmen (KIT Scientific Publishing, 2017)
This comprehensive book provides in-depth knowledge and understanding of design rules according to Eurocode 5. It is based on the first edition of the STEP (Structural Timber Education Programme) series, which was prepared in 1995 by about 50 authors from 14 European countries. The present work updates and extends the STEP compilation and is aimed at students, structural engineers and other timber structure professionals.